2019
DOI: 10.1038/s41598-019-55805-4
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-binding affinity and thermostability of chimeric mouse-chicken IgY and mouse-human IgG antibodies with identical variable domains

Abstract: Constant (C)-region switching of heavy (H) and/or light (L) chains in antibodies (Abs) can affect their affinity and specificity, as demonstrated using mouse, human, and chimeric mouse-human (MH) Abs. However, the consequences of C-region switching between evolutionarily distinct mammalian and avian Abs remain unknown. To explore C-region switching in mouse-chicken (MC) Abs, we investigated antigen-binding parameters and thermal stability of chimeric MC-6C407 and MC-3D8 IgY Abs compared with parental mouse IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In a study conducted in 2019 on the thermal stability of IgG1 antibody, it was found that almost half of the binding activity of the antibody decreased after two minutes at 90°C, and Fab (e.g., ranibizumab) was very sensitive to heat treatment. 26 , 29 , 30 The present results also indicated that half of the antibody activity decreased in in vitro angiogenesis of HUVECs after about five minutes of heating at 100°C, whereas Fab complexation led to higher thermal stability.…”
Section: Resultssupporting
confidence: 65%
“…In a study conducted in 2019 on the thermal stability of IgG1 antibody, it was found that almost half of the binding activity of the antibody decreased after two minutes at 90°C, and Fab (e.g., ranibizumab) was very sensitive to heat treatment. 26 , 29 , 30 The present results also indicated that half of the antibody activity decreased in in vitro angiogenesis of HUVECs after about five minutes of heating at 100°C, whereas Fab complexation led to higher thermal stability.…”
Section: Resultssupporting
confidence: 65%
“…Designing on chimeric antibody could be the next step for IgY-scFv study in order to provide better compatibility of the antibody in the host system, and to recoup the possibly decreased speci city and a nity of antibody fragments as compared to full length antibody. Recent study con rmed that mammalian IgG and avian IgY shared compatible V-C region interfaces, which may be conducive for the design and utilization of mammalian-avian chimeric Abs (24).…”
Section: Discussionmentioning
confidence: 97%
“…It has antibacterial and antiviral effects and can kill or dissolve pathogenic microorganisms with the coordination of complement, so it is an important component of the body to fight diseases. Previous studies reported that the main immunoglobulins in poultry include IgA, IgM and IgG (Mockett 1986;Choi et al, 2019). Usually, IgM is a high molecular weight pentamer with a unit of μ2L2 in serum, and is generally produced in greater abundance than IgG.…”
Section: Comparative Analysis Of Blood Immune Indicesmentioning
confidence: 99%